CBR Correlation with Index and Compaction Properties of Soil - Wahid Sapta; Yudi Harianto; Nurly Gofar (Indonesian Geotechnical Journal, 2023)
California Bearing Ratio (CBR) is widely used in the design of roads to indicate the bearing capacity of subgrade as well as each layer of the flexible pavement system. However, the procedure for obtaining the CBR value is often considered complicated and time-consuming, thus; some correlations were developed by previous researchers between the CBR value and index properties such as fine content (w), liquid limit (LL), and plasticity index (PI) of the soil, as well as between the CBR value and compaction properties i.e., optimum moisture content (OMC) and maximum dry density (MDD). This study was conducted to evaluate the applicability of the published correlation on the soil obtained in Palembang and the surrounding areas. In this case, 30 sets of secondary data were collected and selected from past projects. In addition, laboratory tests were conducted on five sets of samples for verification purposes. The laboratory tests include a wet sieve to obtain fine content, Atterberg limits to determine soil’s plasticity, and a standard Proctor test to obtain OMC and MDD. Analysis shows that with modifications, some published correlations could be used to predict unsoaked and soaked CBR values for soils in Palembang. Furthermore, two correlations were developed between the CBR values and compaction properties of the soil based on statistical analysis of the collected data.